Pengaruh Pembelajaran Akidah Akhlak Terhadap Perilaku Religius Siswa Di Kelas X IPS Man 1 Pasaman Barat - Amelia Sari; Supriadi Supriadi; Fajriyani Arsya; Januar Januar (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
This study is based on the phenomena experienced by social studies students in class X MAN 1 West Pasaman. The researcher saw that at the research site there were still some students who did not live up to the moral creed material. This can be proven when students talk to their friends using impolite words, even heard when talking to their teacher. Then there are students who don't attend congregational prayers, students who don't want to read the Koran, and some are even hostile to their classmates, it's not uncommon for teachers to greet students without answering them. .and there are many other things behind the change or decline in a student's religious behavior. This research is a correlational research with quantitative data orientation. The sample of this research is students of class X IPS MAN 1 Pasaman Barat. There were a total of 80 people. The results showed that the analysis and discussion of the research data took the sig value from the results of hypothesis testing in the coefficient table. 0.000 <0.05, so it can be concluded that the learning variable of morals and faith (X) influences religious behavior. (Y ).